WANPRESTASI PEMBAYARAN KLAIM ASURANSI JIWA AKIBAT KELALAIAN PENYERAHAN BERKAS OLEH MITRA PENANGGUNG SEBAGAI KOLEKTOR PENGAJUAN KLAIM (Studi Kasus Sertifikat Asuransi Polis Nomor 15.001673) - Santini, Inawati (UNES Law Review, 2018)
At this time many banks are incentive to lure consumer credit to consumers. In general, consumer loan interest rate is higher than productive credit, even there is a fixed rate. It seems that the fixed rate makes it easy to organize family finances, paying only monthly installments of the same amount, but if carefully calculated, the interest is much higher. Consumer Loan Protection with Insurance Policy Certificate 15.001673 is a life insurance product that guarantees repayment of the remaining amount of Loans and / or monthly loan installment of the Customer as Participant (Insured) to the Policyholder in case the Participant (the Insured) has a death risk or total temporary disability / Or total permanent disability. Although it is clear about the rights and obligations in the insurance agreement but the reality is very different because it turns out the insurer does not fulfill its obligations in the event of claim submission from the insured. Rejection of insurance claims may be made by the insurer under the pretext of submitting the file beyond the specified time limit. Issues to be studied further is how validation of denial of life insurance claim made by Jasindo in accordance with the insurance policy and existing legislation and whether Partner Error is can be classified as Wanprestasi payment of Insurance Claim for late in submission of policy file No: 15.001673. In conducting research, this research is normative law research that is research having object of study about rule or rule. The objective is to determine the validity of the refusal of insurance claims made by Jasindo in accordance with the existing insurance policies and regulations and to find out the Default Payment of Insurance Claims due to Delayed Submission by Marketing Party as Collector Submission of Claim on Insurance Certificate Number 15.001673